Effect of Perineal Massage on Perineal Trauma: Scoping Review - Purda Listya, Endah; Octaliana, Hasrita; Susanti, Nurul Fatimah (Universitas Islam Jember, 2024)
Perineal massage as a preventative measure has been shown to reduce the risk of perineal injury and positively affect pelvic floor function in the early postpartum period. Perineal massage can protect and reduce the number and severity of tears. It can be performed from the 34th week of pregnancy and can be performed by pregnant women or their partners for 4 minutes 3-4 times a week or 10 minutes once a week. Objective: to obtain information about the effect of perineal massage on perineal trauma. The research design used was a scoping review. The data used to search for literature reviews were PubMed and ScienceDirect with the keywords massage, trauma, and perineum. The data were selected based on the inclusion and exclusion criteria, and the research method used was a randomized controlled trial. The results of the literature review showed that perineal massage is effective in reducing the risk of severe perineal trauma and episiotomy rates during labor.